2020
DOI: 10.1088/1361-648x/abbb41
|View full text |Cite
|
Sign up to set email alerts
|

First principles investigation of electron correlation and Lifshitz transition within iron polynitrides

Abstract: Metal poly-nitrogen compounds are gaining great interests as potential high energy density materials. Several iron polynitrides have been recently synthesized and investigated under high pressure (2018 Nature Communications 9 2756). In this work the electron correlations within these iron poly-nitrogen compounds were self-consistently determined, benchmarked with those obtained from linear response approach. Along with the increase of the concentration of nitrogen, the Coulomb interaction st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…[34][35][36] The U and J values are given as 4.565 and 0.853 eV for Fe-d orbital, respectively, which have been verified to show a good description of the structural and electronic properties for FeN 2 . [37] The electron-ion interactions are described by projector-augmented wave (PAW) potentials. [38] The self-consistent total energy difference and the convergence criterion for forces on atoms are set as 1 Â 10 À5 eV atom À1 and 0.02 eV Å À1 , respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…[34][35][36] The U and J values are given as 4.565 and 0.853 eV for Fe-d orbital, respectively, which have been verified to show a good description of the structural and electronic properties for FeN 2 . [37] The electron-ion interactions are described by projector-augmented wave (PAW) potentials. [38] The self-consistent total energy difference and the convergence criterion for forces on atoms are set as 1 Â 10 À5 eV atom À1 and 0.02 eV Å À1 , respectively.…”
Section: Computational Detailsmentioning
confidence: 99%
“…As shown in literatures, in some cases, applying stress or strain can effectively manipulate the electronic structure and mechanical properties of materials. [ 21–28 ] As for the II–IV–V 2 ceramics, it was recently discovered that XGeN 2 (X = Mg,Zn,Cd) and MSnN 2 (M = Mg,Zn) transit from Pna21$P n a 2_{1}$ structure to Pnma structure under uniaxial compression along [100] direction at a certain value, [ 19,29,30 ] where MgGeN 2 and MgSnN 2 can stabilize at the newly discovered Pnma phase after fully removing the compression. Based on this, thickness‐dependent thin films were constructed and studied on their electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also demonstrated that the band structure of iron‐doped g‐C 3 N 4 is dependent on the doping concentration. [ 6 ] Although there have been many studies on the structure and characteristics of the metal doped g‐C 3 N 4 systems, there are still some concerns, such as the causes and effects of metals on photogenerated carriers’ separation and the electron excitation mechanism. In this work, we present detailed studies on the influence of single metal (K, Ca, Ga, Cu, Ni) doping on the electronic and optical properties of g‐C 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%